Accountability in NGOs: To whom and why should they be accountable? - Chávez Passano, Martha Adriana (2019)
The significant increase in the number of active Non-Governmental Organizations (NGOs), the amount of goods they manage and the different groups interested in their activities, oblige them to be transparent. The literature that will be reviewed helps us to understand, in first place, to whom should NGOs be accountable to, where we find different groups of stakeholders (government, donors, beneficiaries, among others). Nowadays organizations should seek to incorporate accountability as part of their strategy. Accountability should not be only conducted in the financial sphere, but they must also report on their activities, their management, their strategy and their direction. Accountability must also have an internal focus, seeking the participation of interested parties. Finally, we can identify the main forms of accountability categorization.